Enhancing Cross-Functional Collaboration in Hybrid Projects: The Role of Business Analysis Standards in Bridging Predictive and Agile Practices - Ashkan Pourzeinali; Behzad Feizbakhsh; Sathy Srithar (Indonesian Journal of Education And Computer Science, 2025)
Hybrid project approaches that integrate both predictive and agile methods demand successful cross-functional teamwork to deliver successful project outcomes. The research explores how business analysis standards such as the BABOK Guide and the PMI Guide to Business Analysis help improve team collaboration in hybrid project environments. The systematic literature review in the study examines the role BA standards play in supporting stakeholder alignment and shared understanding while bridging communication gaps between technical and non-technical team members. The research indicates that BABOK enhances stakeholders' ability to collaborate while the PMI Guide offers a strategic approach to integrate business analysis with overall project objectives. Business Analysis standards improve project results and teamwork effectiveness even though challenges like resistance to change and tool adaptability remain in agile environments. The study delivers practical recommendations for organizations aiming to boost team coordination and communication in hybrid project environments by utilizing structured business analysis methods.